Photochromic 2,2-Disubstituted Naphthopyrans - A. AL-Sehaibani, Hamad (Asian Journal of Chemistry, 2010)
Novel 2,2-disubstituted naphthepyrans which contain a dimethyl, diphenyl, spiro adamantyl, spirofiuorenyl at position 2, show photochromic compounds which undergo a colourless to colour change in unfiltered sunlight and exhibit a rapid thermal fade at ambient temperaures.